2019
DOI: 10.1002/ajp.23049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold weather on the sleeping behavior of Skywalker hoolock gibbons (Hoolock tianxing) in seasonal montane forest

Abstract: Considering the high energetic costs of maintaining constant body temperature, mammals must adjust their thermoregulatory behaviors in response to cold temperatures. Although primate daytime thermoregulation is relatively well studied, there is limited research in relation to nighttime strategies. To investigate how Skywalker hoolock gibbons (Hoolock tianxing) cope with the low temperatures found in montane forests, we collected sleep-related behavior data from one group (NA) and a single female (NB) at Nankan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Huddling helps thermoregulation by increasing body temperature (Japanese macaques, Macaca fuscata: Hanya et al 2007). For example, skywalker hoolock (Hoolock tianxing) and black crested (Nomascus concolor jingdongensis) gibbons huddle together more frequently in the cold season (Fan and Jiang 2008;Fei et al 2019). Similarly, Azara's owl monkeys (Aotus azare azare) do not sleep in huddles when temperatures are relatively high (Savagian and Fernandez-Duque 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Huddling helps thermoregulation by increasing body temperature (Japanese macaques, Macaca fuscata: Hanya et al 2007). For example, skywalker hoolock (Hoolock tianxing) and black crested (Nomascus concolor jingdongensis) gibbons huddle together more frequently in the cold season (Fan and Jiang 2008;Fei et al 2019). Similarly, Azara's owl monkeys (Aotus azare azare) do not sleep in huddles when temperatures are relatively high (Savagian and Fernandez-Duque 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Primate sleeping site selection, however, is unlikely to be solely driven by predator avoidance, with variables such as distance to food (Fan and Jiang 2008), range defence (Heymann 1995), thermoregulation (Fei et al 2019), comfort and protection from the elements and parasites (Largo 2009;Whitten 1982), also likely to be non-mutually exclusive influencing factors. Sleeping sites may be selected at the edge of the home range to facilitate range defence (Day and Elwood 1999) or nearer to the centre of the home range to avoid inter-group aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Social huddling at sleeping trees may be an additional strategy used by Bale monkeys to cope with cold weather, supporting the thermoregulation hypothesis. Black crested gibbons (Nomascus concolor), Skywalker hoolock gibbons (Hoolock tianxing), and Japanese macaques (Macaca fuscata) often huddle when it is cold (Fan & Jiang, 2008;Fei et al, 2019) and that huddling reduces energy loss and increases body temperature (Hanya et al, 2007). In fact, a study of southern bamboo lemurs (Hapalemur meridionalis) inhabiting a degraded fragment with a few remaining large trees in Madagascar showed that social huddling is more important than sleeping or resting place selection within trees to cope with environmental variables such as rainfall, wind, and cold air (Eppley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%